Enhanced membrane electrode assembly performance by adding PTFE/Carbon black for high temperature polymer electrolyte membrane fuel cell. (18th August 2021) - Kim, Do-Hyung; Jung, Hyeon-Seung; Chun, Hyunsoo; Pak, Chanho
Abstract: Phosphoric acid used as a proton-conductive medium in high-temperature polymer electrolyte membrane fuel cells (HT-PEMFCs) poisons the Pt surface and prevents oxygen transport in the cathode catalyst layer. The hydrophobic binders in the catalyst not only maintain the catalyst layer structure but also control the phosphoric acid distribution. In this study, polytetrafluoroethylene (PTFE)/carbon black (Vulcan XC-72R) added to the catalyst layer generates an oxygen transport channel. The catalyst layers coated on the gas diffusion layer by the bar-coating method serve as the cathode. High PTFE content causes hydrophobicity in the catalyst layer. The membrane electrode assembly (MEA) with 6 wt% PTFE/Vulcan results in the highest peak power density (0.347 W cm −2 ) and voltage (0.653 V) at 0.2 A cm −2 . A critical reason for its high performance is having the lowest Rct + Rmt values measured at 0.6 V and 0.4 V. These results could contribute to improving the MEA performance for HT-PEMFCs. Highlights: High PTFE content causes hydrophobicity in the catalyst layer. PTFE in the catalyst improved membrane electrode assembly performance. PTFE/Vulcan successfully allowed oxygen transport. Too high PTFE content decreased proton conductivity